Influence of Pile Foundation Stiffness on Column Design in One-Story Reinforced Concrete Frames - Ireneusz Dyka; Krzysztof Klempka (Applied Sciences, 2023)
When designing reinforced slender columns for the lowest story of buildings, all factors that may affect the load-bearing capacity should be considered. One is the increase in the bending moment value caused by the rotation of the supporting foundation. The geotechnical parameters of subsoil stiffness and the method of calculating foundation displacements are the main influences. This problem applies to both shallow foundations and pile foundations. The article presents this issue in relation to pile foundations in multilayered subsoils and also the method and examples of second-order calculations that take into account the influence of pile support and columns’ nominal stiffness. The results showed that taking into account the stiffness of the pile foundation has an impact on the increase in bending moments in the columns, and this cannot be ignored in the design. The presented method allows for a precise, safe and optimal design of concrete columns supported by foundations on multilayered subsoils.